1981
DOI: 10.1111/j.1365-2133.1981.tb00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Neutron activation analysis of trace elements in skin. IX. Rubidium in normal skin

Abstract: SUMMARY Regional variations of levels of rubidium (Rb) in normal adult skin were determined by non‐destructive neutron activation analysis combined with gamma spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…In human skin, the concentration of zinc is higher in the epidermis (50-70 µg/g dry weight) compared to the dermis (10-15 µg/g dry weight). This difference may reflect the involvement of zinc-dependent RNA and DNA polymerases in the mitotically active basal cells [299][300][301][302]. Immunohistochemical and in situ hybridization localization studies have revealed that in normal skin, high levels of metallothionein (MTs) are found in the basal epidermis, while their concentrations are reduced in postmitotic keratinocytes, reticuloendothelial cells, and fibroblasts [303][304][305].…”
Section: Zinc (Zn)mentioning
confidence: 99%
“…In human skin, the concentration of zinc is higher in the epidermis (50-70 µg/g dry weight) compared to the dermis (10-15 µg/g dry weight). This difference may reflect the involvement of zinc-dependent RNA and DNA polymerases in the mitotically active basal cells [299][300][301][302]. Immunohistochemical and in situ hybridization localization studies have revealed that in normal skin, high levels of metallothionein (MTs) are found in the basal epidermis, while their concentrations are reduced in postmitotic keratinocytes, reticuloendothelial cells, and fibroblasts [303][304][305].…”
Section: Zinc (Zn)mentioning
confidence: 99%